﻿Production of rare cycloartane saponins from Astragalus thracicus (Griseb) compared to Astragalus membranaceus (Fisch.) Bunge - native and biotechnological sources - Preslav Enchev; Yancho Zarev; Hans Michler; Iliana Ionkova (Pensoft Publishers, 2023)
The aim of this study is a comparative metabolomic analysis between the endangered species Astragalus membranaceus and endemic species Astragalus thracicus concerning cycloartane saponins. In addition, in vitro shoots, callus, and suspension cultures of A. thracicus were successfully established to conserve the biodiversity of those endemic species and to increase the amount of produced saponins. The comparison was made according to the quantity of cycloartane saponins astragaloside I (1), astragaloside II (2), and astragaloside IV (4) to the reference standards for the same compounds by UHPLC-HRESI-MS analysis. The in vitro root cultures of A. thracicus reached two folds higher amounts of saponins (1.50 mg/g DW (1), 1.01 mg/g DW (2), and 0.91 mg/g DW (3)) than the native root of A. thracicus (1.14 mg/g DW (1) 0.47 mg/g DW (2), 0.40 mg/g DW (3)), and up to six times higher when compared with roots A. membranaceus (0.23 mg/g DW (1), 0.18 mg/g DW (2) and 0.05 mg/g DW (3)).